Sanaugait in nunavut - Buis, A. (Alena); Smith, S.E.K. (Sarah E. K.) (The Journal of Modern Craft, 2013)
Starting from the recent promotion of the inuksuk, which was crowned the official logo of the 2010 Vancouver Olympic Games, this article examines the ways in which Inuit culture is currently being deployed within Canada and to what ends. We focus our examination on sanaugait, the Inuktitut term for things created by hand, which encompasses what is conventionally labeled craft production. Structuring our discussion around two case studies, we first delve into the artistic practice of Inuk textile artist and arts administrator Theresie Tungilik. This analysis reveals how Tungilik employs fiber arts to engage with oral histories and to comment on the production of sanaugait historically. Subsequently, we address the changes in the management of visual and material culture in Nunavut, Canada's newest territory, which was established in 1999. Examining territorial policy and strategies, we assess how sanaugait have been harnessed for specific economic growth. Through our examination of sanaugait as they have been mobilized by individual artists, as well as territorial and federal governments, we suggest that craft production is central to a renegotiation of power. Specifically, we argue that sanaugait reveal a shift in control between the predominantly Inuit territorial government and the Canadian federal government.